2015
DOI: 10.1016/j.jmb.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Antiparallel β-Sheet Structure within the C-Terminal Region of 42-Residue Alzheimer's Amyloid-β Peptides When They Form 150-kDa Oligomers

Abstract: Understanding the molecular structures of amyloid-β (Aβ) oligomers and underlying assembly pathways will advance our understanding of Alzheimer’s disease (AD) at the molecular level. This understanding could contribute to disease prevention, diagnosis, and treatment strategies, as oligomers play a central role in AD pathology. We have recently presented a procedure for production of 150 kDa oligomeric samples of Aβ(1–42) (the 42-residue variant of the Aβ peptide) that are compatible with solid state NMR analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
84
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 56 publications
(106 reference statements)
10
84
1
Order By: Relevance
“…Subsequent NMR analysis determined that in this oligomer population, C-terminal b-sheet (residues 22-39) was included into the secondary structure formation, whereas the N-terminal half of the peptide was unstructured due to the EGCG binding [32]. In Ab 42 oligomers formed in the presence of SDS, residues 25-40 were found to form b-strands that were arranged in the antiparallel fashion, whereas the structure of the N-terminal half of the peptide was unclear [14,18]. An EPR investigation of oligomers prepared under the similar conditions indicated gradual increase in the structural order towards the C-terminus of the peptide and antiparallel arrangement of b-strands [18].…”
Section: Amyloid B Oligomersmentioning
confidence: 86%
“…Subsequent NMR analysis determined that in this oligomer population, C-terminal b-sheet (residues 22-39) was included into the secondary structure formation, whereas the N-terminal half of the peptide was unstructured due to the EGCG binding [32]. In Ab 42 oligomers formed in the presence of SDS, residues 25-40 were found to form b-strands that were arranged in the antiparallel fashion, whereas the structure of the N-terminal half of the peptide was unclear [14,18]. An EPR investigation of oligomers prepared under the similar conditions indicated gradual increase in the structural order towards the C-terminus of the peptide and antiparallel arrangement of b-strands [18].…”
Section: Amyloid B Oligomersmentioning
confidence: 86%
“…A variety of oligomeric and protofibrillar states have been partially characterized by ssNMR (Ahmed et al 2010; Scheidt et al 2011; Lopez del Amo et al 2012; Scheidt et al 2012; Tay et al 2013; Lendel et al 2014; Sarkar et al 2014; Huang et al 2015; Parthasarathy et al 2015; Potapov et al 2015). The main finding, originally reported by Ishii and coworkers (Chimon and Ishii 2005; Chimon et al 2007), is that the Aβ conformation in nonfibrillar intermediates is remarkably similar to the conformation in fibrils.…”
Section: Molecular Structures Of Transient and Metastable Aβ Aggregatesmentioning
confidence: 99%
“…A detailed model a metastable Aβ protofibril has also been developed from ssNMR data (Qiang et al 2012). Complete models for oligomeric Aβ assemblies have not yet been developed, but a substantial body of experimental data has been obtained for samples with a variety of morphologies, prepared under a variety of in vitro conditions (Chimon and Ishii 2005; Chimon et al 2007; Ahmed et al 2010; Scheidt et al 2011; Lopez del Amo et al 2012; Scheidt et al 2012; Tay et al 2013; Lendel et al 2014; Sarkar et al 2014; Huang et al 2015; Parthasarathy et al 2015; Potapov et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the native protein structure, amyloid fibrils show common features with protein β-strands arranged perpendicular to the elongation axis. However, recent studies suggested that their toxicity may be related to certain differences in the fibril structural and biochemical properties [2,3]. Unfortunately, a precise relation between fibril polymorphism, resulting from aggregation of monomers and oligomers with different conformational properties, and toxicity is difficult to assess [4].…”
Section: Introductionmentioning
confidence: 99%